Association of alcohol consumption with abortion among ever-married reproductive age women in Ethiopia: A multilevel analysis - Ayana, Galana Mamo; Raru, Temam Beshir; Deressa, Alemayehu; Regassa, Lemma Demissie; Gamachu, Mulugeta; Negash, Belay; Birhanu, Abdi; Merga, Bedasa Taye (Frontiers in Global Women's Health, 2022)
Background A miscarriage or a spontaneous loss of a pregnancy that occurs before the 20th week is an abortion. Even though numerous recommendations state that pregnant women should abstain from alcohol at all stages of pregnancy, alcohol intake among pregnant women is common. However, there are few papers addressing the effect of alcohol use on miscarriage using nationally representative data. Moreover, the association of alcohol use with abortion and its mechanisms is not well studied in the Ethiopian region. Therefore, the objective of the current study was to estimate the association of alcohol use with abortion rates among reproductive age (15–49) women in Ethiopia. Methods Using the most recent findings of the Ethiopian Demographic and Health Survey (EDHS), secondary data analysis was performed among pregnant women in Ethiopia. A total of 11,396 women between the ages of 15 and 49 years who were of reproductive age were included in the research. To characterize the study population, descriptive statistics were used. The variability was considered using the multilevel binary logistic regression model. A multilevel binary logistic model was used to determine the effect of alcohol intake on abortion while controlling for potential confounders. In the multivariable analysis, variables with a P-value of less than 0.05 were considered statistically significant for the response variable. Results The proportion of women who had an abortion was 10.46% with a 95% CI of 9.92–11.03. In the ﬁnal model of the multilevel analysis, age group [adjusted odds ratio (AOR) = 6.13; 95% CI: 3.86–9.73], education level (AOR = 1.29; 95 and CI: 1.10–1.51), alcohol consumption (AOR = 1.38; 95% CI: 1.18–1.61), age at first sex (AOR = 1.20; 95% CI: 1.03–1.39), media exposure (AOR = 1.28, CI: 1.10–1.48), contraceptive use (AOR = 1.34, CI: 1.16–1.56), and occupation of respondent (AOR = 1.21, CI: 1.06–1.38) were identified to be significant determinants of abortion in Ethiopia. Conclusion Sexual and reproductive health education and family planning programs should target older women in the reproductive age group, women with primary educational status, working women, and those who initiated sexual intercourse at a younger age considering it could reduce abortion and unintended pregnancy. Furthermore, as part of sexual and reproductive health education, the adverse effect of alcohol consumption on abortion should be emphasized.